Thermal evaporation furnace with improved configuration for growing nanostructured inorganic materials - Joanni, E.; Savu, R. [UNESP]; Valadares, L.; Cilense, M. [UNESP]; Zaghete, M. A. [UNESP] (American Institute of Physics (AIP), 2011)
A tubular furnace specifically designed for growing nanostructured materials is presented in this work. The configuration allows an accurate control of evaporation temperature, substrate temperature, total pressure, oxygen partial pressure, volumetric flow and source-substrate distance, with the possibility of performing both downstream and upstream depositions. In order to illustrate the versatility of the equipment, the furnace was used for growing semiconducting oxide nanostructures under different deposition conditions. Highly crystalline indium oxide nanowires with different morphologies were synthesized by evaporating mixtures of indium oxide and graphite powders with different mass ratios at temperatures between 900 degrees C and 1050 degrees C. The nanostructured layers were deposited onto oxidized silicon substrates with patterned gold catalyst in the temperature range from 600 degrees C to 900 degrees C. Gas sensors based on these nanowires exhibited enhanced sensitivity towards oxygen, with good response and recovery times. (C) 2011 American Institute of Physics. [doi:10.1063/1.3597577]